Afghanistan Public Sector Pension Scheme : From Crisis Management to Comprehensive Reform Strategy - Sluchynsky, Oleksiy (World Bank, Washington, DC, 2014)
After years of dealing with pension policy in crisis management mode, the Government of Afghanistan has begun the process of formulating a national pension policy based on a long-term vision. Until very recently the Government had been focused on short-term policy actions to alleviate growing pressure on the budget. While these measures were necessary, pension policy must take a long term view. Recently, the Government has developed a comprehensive reform package and initiated the process of legal drafting. A reformed system must have clear objectives, be fiscally sustainable, and address needs of various population groups. The final choices will need to be made as to mandate and design and administrative arrangements of the reformed system. The challenge is to ensure that the measures taken in the next few years do not make it more difficult to pursue certain preferred policies later. This paper shows that, according to the financial projections, there is now a window of opportunity for implementing a reform of the system.